2012
DOI: 10.1111/j.1420-9101.2012.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection uncouples the evolution of brain and body size in pinnipeds

Abstract: The size of the vertebrate brain is shaped by a variety of selective forces. Although larger brains (correcting for body size) are thought to confer fitness advantages, energetic limitations of this costly organ may lead to trade-offs, for example as recently suggested between sexual traits and neural tissue. Here, we examine the patterns of selection on male and female brain size in pinnipeds, a group where the strength of sexual selection differs markedly among species and between the sexes. Relative brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 78 publications
(162 reference statements)
2
51
1
Order By: Relevance
“…Pinnipeds are rarely included in analyses of carnivoran brain evolution. This extensive analysis suggests that the brain-body relationship in pinnipeds is driven much more by body size evolution than in their terrestrial and arboreal relatives, which may also reflect the extreme sexual dimorphism in body size observed in some species (35). Our results suggest that for most carnivorans, changes in relative brain size reflect, in large part, body size evolution rather than selection for neuronal capacity.…”
Section: Isometry Represents Allometry Y Y X Xmentioning
confidence: 69%
See 1 more Smart Citation
“…Pinnipeds are rarely included in analyses of carnivoran brain evolution. This extensive analysis suggests that the brain-body relationship in pinnipeds is driven much more by body size evolution than in their terrestrial and arboreal relatives, which may also reflect the extreme sexual dimorphism in body size observed in some species (35). Our results suggest that for most carnivorans, changes in relative brain size reflect, in large part, body size evolution rather than selection for neuronal capacity.…”
Section: Isometry Represents Allometry Y Y X Xmentioning
confidence: 69%
“…Our results suggest that for most carnivorans, changes in relative brain size reflect, in large part, body size evolution rather than selection for neuronal capacity. It has been similarly suggested that changes in body size may drive life history evolution in carnivorans (35,36), and the framework presented here will allow for rigorous testing of this and other hypotheses concerning the mechanisms underlying macroevolutionary trends. Whether the inclusion of fossils adds valuable information to macroevolutionary studies of brain and body size evolution or not remains a moot point.…”
Section: Isometry Represents Allometry Y Y X Xmentioning
confidence: 86%
“…These same regressions were nearly identical for males between the two food treatments (Figure 4). These regressions also indicate that the significant differences in relative brain size between food levels and the significant “sex × food” interaction are not likely due to increased canalization of brain size versus body size (see Fitzpatrick et al., 2012). The food treatments include fish that exhibit a similar range of variation in size, and the overall differences in body size between high‐ and low‐food levels for males and females are nearly identical (average ln male body size (g): HF = −1.28, LF = −1.52; average ln female body size (g): HF = −0.18, LF = −0.42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent success in using brain components to understand the evolution of brain macromorphology [Sakai et al, 2011;Swanson et al, 2012;Gómez-Robles et al, 2014] and particular behaviors [de Winter and Oxnard, 2001], together with the realization that cell density and connectivity differ substantially among mammals [HerculanoHouzel et al, 2007[HerculanoHouzel et al, , 2011Sarko et al, 2009;Huang et al, 2014], also suggest that overall brain size may be too vague a predictor of cognitive ability. There is mounting evidence that relatively large brains often arise through selection for a smaller body size, rather than larger brain size [Fitzpatrick et al, 2012;Smaers et al, 2012;Swanson et al, 2012], so that in many cases no cognitive selectors of large brain size may exist.…”
Section: Discussionmentioning
confidence: 99%